Secukinumab - Nilgün Atakan (Galenos Publishing House, 2022)
Secukinumab is a human immunoglobulin G1/κ monoclonal antibody targeting interleukin-17A. In clinical trials, 77-81% of the secukinumab patients achieved a PASI75 response in 12 weeks. As well as in chronic plaque psoriasis, secukinumab has also been found effective and safe as monotherapy in nail and hairy skin psoriasis and psoriatic arthritis. Secukinumab should be used with caution in patients or their first-degree relatives who have inflammatory bowel disease. It has a safe side effect profile in terms of latent tuberculosis activation.